Online-to-Offline Marketing (O2O: Strategies to Increase Sales Conversion - Popo Suryana (Jurnal Info Sains : Informatika dan Sains, 2023)
The phenomenon of shifting consumer behavior from online to offline requires adjustments to marketing strategies for business people. This research will explore various O2O methods that can be used to integrate online and offline shopping experiences to increase consumer trust, expand market reach, and optimize sales conversion rates. So the aim of this research is to analyze and identify Online-to-Offline (O2O) marketing strategies that are effective in increasing sales conversions. This research uses a qualitative approach with descriptive methods. The research results show that implementing Online-to-Offline (O2O) marketing strategies can effectively increase sales conversions and customer engagement. By integrating online and offline shopping experiences, companies can provide added value to consumers, overcome online shopping barriers, and create closer relationships with customers. Integrated customer service support, promotion of events promoted online, and initiatives to encourage customers to share their experiences online are key factors in the success of an O2O strategy. Thus, this research emphasizes the importance of adapting to the dynamics of consumer shopping in the digital era to achieve sustainable marketing and sales success.